Crystallographic Characterisation of Ultra-Thin, or Amorphous Transparent Conducting Oxides—The Case for Raman Spectroscopy - Caffrey, David; Zhussupbekova, Ainur; Vijayaraghavan, Rajani K.; Ainabayev, Ardak; Kaisha, Aitkazy; Sugurbekova, Gulnar; Shvets, Igor V.; Fleischer, Karsten (MDPI, 2020)
The electronic and optical properties of transparent conducting oxides (TCOs) are closely linked to their crystallographic structure on a macroscopic (grain sizes) and microscopic (bond structure) level. With the increasing drive towards using reduced film thicknesses in devices and growing interest in amorphous TCOs such as n-type InGaZnO4 (IGZO), ZnSnO3 (ZTO), p-type CuxCrO2, or ZnRh2O4, the task of gaining in-depth knowledge on their crystal structure by conventional X-ray diffraction-based measurements are becoming increasingly difficult. We demonstrate the use of a focal shift based background subtraction technique for Raman spectroscopy specifically developed for the case of transparent thin films on amorphous substrates. Using this technique we demonstrate, for a variety of TCOs CuO, a-ZTO, ZnO:Al), how changes in local vibrational mo
Keywords: transparent conducting oxide; TCO; Raman spectroscopy; amorphous oxide; oxide electronics; background subtraction